Modification of soil structure of sand tailings: 2. effect of silt, sand and clay contents on aggregate development using organic amendments - A. M., Mokhtarudin; Subari, Zulkifli (Universiti Putra Malaysia Press, 1996)
The effect of skeletal materials (silt and very fine sand) and clay on aggregate formation and stabilization of organically amended sand tailings (99% sand) was investigated. In this experiment, sand tailings were mixed with different proportions ofslime (slime contains 37% silt + very fine sand and 33% clay) and then treated with palm oil mill effluent (POME) cake at the rate of 10.5 g of POME cake per 1200 g of sand-slime mixture. The mixtures were incubatedfor 2 weeks and then air-dried. The extent of aggregation of the samples was determined by dry sieving, and the aggregate stability by wet sieving. The addition of silt + very fine sand and clay improved aggregation and aggregate stability of the sandy soils. The optimum amount of clay required to achieve a good aggregation and aggregate stability for the amount of organic matter added is 25%, where the increase in stability was seven-fold over the control. With slime, which contains 33% clay, this amount of clay can be achieved from a mixture of 75% slime + 25% sand tailings. This mixture contains 32% skeletal materials.